ANALISI PEMAHAMAN KONSEP OPERASI BILANGAN BULAT PADA SISWA KELAS IV MELALUI PEMBELAJARAN DARING - Shafira Yaumil Alin; Heni Pujiastuti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article explains the ability of students to understand the concept of integer counting operations in online learning. The research was conducted in the even semester of 2020/2021. The location of the research was one of the elementary schools in Kragilan Serang Banten. The population of the research involved 15 fourth-grade students as the sample ofdata. Data collection techniques used observation techniques and tests of mathematical understanding concept abilities. The research method used was a qualitative research design. Data were analyzed by using data reduction and ata presentation. And the conclusions that referred to the indicators of understanding concept achievement were (1) 73% of students who were able to restate a concept, (2) 53% of students who could classify group objects based onthe concept, (3) 47% of students who were able to provide whether examples and not examples of concepts those were, (4) 87% of students who were able to present concepts in various forms of mathematical representation, (5) 40% of students who could develop the necessary and sufficient requirements of the concept, (6) 13% of students who could use, utilize and choose a particular procedure or operation, and (7) 20% of students who could apply the concepts oralgorithms into problem-solving. Contextual mathematics learning could be applied by teachers when giving material, because contextual learning was expected to help students easily understand the concept of numerical operations that was started from students' daily activities.